Features of the legal status of control and supervision authorities in land use and protection (on the example of the Russian Federation) - Іщук, Юрій Віталійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article analyzes the characteristics of the legal status of the inspection bodies in the field of land use and protection (on the example of the Russian Federation). Author also investigates the functioning of this authorities' system in the Russian Federation, studies proposals and recommendations aimed at improving the inspection bodies in the use and protection of the land.